Jenny Thompson (Breathing Stroke) at 35 m of Her Leg of the Gold Medal 4 x 100 m Medley Relay Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (12 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson (Breathing Stroke) at 35 m of Her Leg of the Gold Medal 4 x 100 m Medley Relay Race at the 1998 Perth World Championships. Jenny Thompson's butterfly stroke contains good features. Improvements could come from a wider entry, which would result in less inertial lag before direct propulsion was developed. That entry would also reduce her moderate "diving." Both features would result in faster swimming and a technique that would be well suited to both 100-m and 200-m events.